Primary Umbilical Endometriosis: A Rare Entity - Roy, Moumita (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Primary umbilical endometriosis is a rare benign gynaecological disorder caused by ectopic endometrial tissue in the umbilicus. The disease typically manifests as a painful umbilical nodule associated with cyclic bleeding or discharge during menstruation. Here, a 46-year-old woman with low parity and without previous history of abdominal surgery has been reported who presented with cyclical per-umbilical bleeding and pain in the umbilical region during menstruation without any palpable umbilical nodule. The patient responded well to initial medical management, but symptoms recurred on discontinuation of the medication. Though clinically, there was no palpable nodule, and ultrasonography revealed a hypoechoic lesion in the lower umbilical region suggestive of endometrial deposition. On resuming medical management, her symptoms abated. J Bangladesh Coll Phys Surg 2023; 41: 173-176